The instrument of authority: The Niger river as propaganda in Northern Nigeria, 1900-1905 - Rensen, Bas (Student Undergraduate Research E-journal!, 2016)
This paper discusses the ways in which Frederick Lugard used the Niger river and her subsidiaries as a tool to secure funding from Great Britain between 1900-1905. The annual reports written by Lugard were propaganda to convince Parliament of the value of the Nigerian project by showing progress towards the installation of “legitimate commerce”. This paper proves that the British were, especially in these early years of colonisation, to a great degree confined to the Niger river. Three cases are analysed to show to what extent Lugard is bound to the river for his propaganda: the abolition of illegitimate trade, the promotion of Nigeria to replace the USA and India as the new centre for cotton farming, and the redirection of commerce from the trans-Saharan route to the English sphere. This paper concludes that the river held an abstract value for the British coloniser: apart from being the major highway for trade and transport, it was also an important tool for Lugard’s propaganda.